Three complete mitochondrial genomes of straw-rotting edible fungus Volvariella volvacea using next generation sequencing. Issue 2 (3rd July 2018) - Wan, Jianing; Li, Yan; Wang, Hong; Tang, Lihua; Li, Zhengpeng; Zhou, Chenli; Tan, Qi; Bao, Dapeng; Yang, Ruiheng
Abstract: The straw-rotting edible fungus Volvariella volvacea is a widely cultivated edible fungus across China and Southeast Asian countries. Three complete mitochondrial genomes of V. volvacea from China, Thailand, and India were determined using the next-generation sequencing technology. The genome sizes of the three strains (China, Thailand, and India) were 62, 541 bp, 64, 531 bp, and 65, 668 bp with GC contents of 38.46%, 38.56%, and 38.52%, respectively. All the genomes encoded 14 conserved protein-coding genes, the small ribosomal RNA subunits (rns), large ribosomal RNA subunits (rnl), and 23 tRNAs were located on the same strand. In the putative protein-coding genes, four introns were distributed in cox1 in the genomes of V23-1 and V8. 5 introns (four introns invaded into cox1and one intron invaded into cob) were detected in Tai8. The phylogenetic analysis confirmed that V. volvacea was a number of Agaricales. This mitochondrial genome may open new avenues for understanding the phylogeny and evolution of Pluteaceae and Agaricales.